Keterbatasan Ekonomi dan Akses Pendidikan Pada Remaja Muslim di Kawasan Marginal - Arinal Inayah (IEMJ: Islamic Education and Management Journal, 2026)
This study aims to explore the impact of economic constraints on access to education for Muslim adolescents in Sugiharjo Village, Tuban Regency. This qualitative, case-study-based research utilised data obtained through informal interviews, participant observation, and document analysis. The findings indicate that  conditions of poverty have created barriers to educational access for Muslim adolescents in Sugiharjo Village, such as dropping out of school, and the choice of low-cost schools with poor facilities or substandard teaching in order to make education affordable. The contribution of this research lies in the development of an innovative conceptual framework that integrates psychological-spiritual dimensions with people's economic strategies as a new basis for inclusive education policies in marginal areas.